2018
DOI: 10.2478/arsm-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Blood Viscosity in Patients with Diabetic Nephropathy Versus Blood Viscosity in Healthy Patients

Abstract: Diabetic nephropathy is the major cause of severe renal impairment and even chronic terminal renal failure requiring dialysis. Blood viscosity is clearly modified in diabetic patients, and particularly in those with severe renal impairment The purpose of this study is to highlight blood viscosity values at different shear rates in patients with diabetic nephropathy compared to the control group. There is a significant increase in blood viscosity in patients with definite renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Diabetes-related micro-vascular diseases have been shown to be closely associated with alteration of hemorheological properties such as increased blood viscosity (Monica et al, 2019), reduced cellular deformability (Brown et al, 2005), and increased cellular aggregation (Foresto et al, 2000). In addition, hemorheological alterations are frequently observed in the early onset of diabetes (MacRury and Lowe, 1990), and it has been suggested that these altered hemorheological properties may precede the growth of diabetic vascular complications (Martinez et al, 1998).…”
Section: Impact Of Diabetic Mellitus On Hemorheologymentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes-related micro-vascular diseases have been shown to be closely associated with alteration of hemorheological properties such as increased blood viscosity (Monica et al, 2019), reduced cellular deformability (Brown et al, 2005), and increased cellular aggregation (Foresto et al, 2000). In addition, hemorheological alterations are frequently observed in the early onset of diabetes (MacRury and Lowe, 1990), and it has been suggested that these altered hemorheological properties may precede the growth of diabetic vascular complications (Martinez et al, 1998).…”
Section: Impact Of Diabetic Mellitus On Hemorheologymentioning
confidence: 99%
“…Both parameters represent reduced deformability, increased aggregation of RBCs, and elevated fibrinogen concentration. Furthermore, the effects of these parameters has been considered in relation to whole blood, and also showed a close correlation with DN (Monica et al, 2019). However, whole blood viscosity is complex, with hemorheological parameters affected due to various factors non-related to diabetes mellitus.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…There have been many studies reporting increases in blood viscosity to be an independent risk factor [18,19]. Parameters such as dyslipidemia, DM, smoking, hematocrit level, erythrocyte deformability and fibrinogen all affect blood viscosity [20].…”
Section: Discussionmentioning
confidence: 99%